Transformações do eu na velhice : estudo psicanalítico sobre algumas consequências psíquicas e para a prática clínica - Vanessa Biscardi Matos (2019)
This work deals with the modifications of the self in old age, its possible consequences for the subject and for the conduct of the psychoanalytic treatment, from the theory of generalized seduction. Taking as a starting point the clinical observation of the recurrence with which, in some care of the elderly, interventions are more necessary in order to synthesize than interpretations for purposes of analysis, we question what occurs in terms of psychic functioning, as well as management possibilities and technique for conducting psychoanalytic treatment in these cases. We hypothesize that, while on the one hand the unconscious does not change in terms of its characteristics and functioning, on the other hand, the experience of old age for some elderly people causes particular transformations of the self that interfere both in the processes of subjectivation and in the conduction of the clinical case by the psychoanalyst. The results are presented in two articles. In the first, we describe the current demographic panorama, which is also a justification for the ethical commitment of theorizing theories that provide a foundation for the psychoanalytic care of the elderly; we present a conceptualization of the term old age, which is external to psychoanalysis and important for our work proposal; we articulate this concept to psychoanalytic theory; and we make a reading of the book "a máquina de fazer espanhóis", by valter hugo mãe (2016), in the form of a clinical listening, using its elements to propose our theoretical developments based on Jean Laplanche's theory of generalized seduction. In the second article, we start from the proposition that old age, in a given moment, imposes an update of enigmatical messages and modifications of the self, which is experienced by some subjects in a traumatic way. Based on the theoretical construction of generalized seduction theory, as well as the text "Inhibitions, Symptoms and Anxiety" (Freud, 1926/ 1996) about this update of enigmatical messages and the egoic modifications, we address the psychoanalytic care of these subjects. We conclude that the consequences of old age experienced with psychic pain and manifested in the clinic as traumatic, require a peculiar management. To think of psychoanalytic treatment in these cases, where the traditional clinic of hysterical and obsessive neuroses are not enough, led us to the analyst’s proposition as a witness (Gondar, 2017) along with his position as enigma's keeper (Laplanche 1993).